PERANCANGAN UI/UX APLIKASI PENGAJUAN CUTI DENGAN METODE DESIGN THINKING - Yuniarti, Angger Styo; Kurniawan, Muhammad Arif; Rukmana, Andy (Universitas Insan Pembangunan Indonesia, 2024)
The application of technology in the company does not only buying and selling transactions. However, in terms of employee recruitment and the human resource, also take advantage of this technology. Procedure for request on leave at company XYZ is still manually. To create an application that is easy to use and what is needed, it is necessary to UI-UX design using the Design Thinking method. Based on the results of research conducted by applying the design thinking method in the UI-UX design process for request on leave, It was concluded that create UI-UX design can help developers to create mobile applications as needed by users especially employees at PT. XYZ.